Sinergi Ekstrak Buah Cengkeh (Syzygium Aromaticum) Dengan Amoksisilin dan Siprofloksasin Terhadap Bakteri Resisten - Patandung, Rosliana; Ariastuti, Reni; Subiyanto, Abyasa Fajari; Ilmi, Ibnul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Antibiotic resistance is a serious global health threat, leading to increased morbidity, mortality, and economic burden due to the reduced effectiveness of infection therapy. One promising strategy to overcome this problem is the combination of antibiotics with natural phytochemical compounds that can enhance antibacterial activity. This study aimed to evaluate the synergistic potential between the ethanol extract of clove fruits (Syzygium aromaticum) and the antibiotics amoxicillin and ciprofloxacin against resistant Staphylococcus aureus and Escherichia coli. The study was conducted in vitro, including clove fruit extraction using 70% ethanol, determination of the minimum inhibitory concentration (MIC) by microdilution, and combination testing using the checkerboard assay to calculate the Fractional Inhibitory Concentration (FIC) index. The results showed that clove extract exhibited antibacterial activity with MIC values of 2000 µg/mL against S. aureus and 4000 µg/mL against E. coli. The combination of clove extract with amoxicillin produced a ΣFIC value of 0.25 (strong synergy), while the combination with ciprofloxacin yielded a ΣFIC of 0.50 (additive effect). These findings indicate that phytochemical constituents in clove, particularly eugenol, may enhance bacterial membrane permeability, thereby strengthening antibiotic activity. This study demonstrates the potential of clove extract as a natural adjuvant to improve the efficacy of antibiotics against resistant bacteria. The practical implication of this result is the opportunity to develop phytochemical–antibiotic combination formulations in pharmaceutical dosage forms that are more efficient and sustainable.